On the relationship of the observed acoustical and related non-acoustical behaviours of nanofibers membranes using Biot- and Darcy-type models. (August 2021) - Hurrell, A.; Horoshenkov, K.V.; King, S.G.; Stolojon, V.
Abstract: There is a general lack of publications on the acoustical and related non-acoustical properties of nanofibrous media. This work attempts to contribute to this gap and to highlight problems associated with acoustic and related non-acoustic characterisation of these materials. The work, presumably for the first time, applies Biot- and Darcy-type mathematical models to explain the observed acoustical and related non-acoustical behaviours of the nanofibres. It identifies theoretical gaps related to the physical phenomena which can be responsible for the observed acoustical behaviours of nanofibrous membranes and it presents recommendations to fill these gaps. The novelty of this work is in the use of a robust theoretical model to explain the measured acoustical behaviour of thin nanofibrous membranes placed on a foam substrate. With this model the actual flow resistivity of nanofibers is estimated from acoustical data. It is demonstrated that a classical model for the flow resistivity of fibrous media does not work when the Knudsen number becomes greater than 0.02, i.e. then the diameter of nanofibres becomes comparable with the mean free path.